Plant products and insecticides effective against Gujhia weevil, Tanymecus indicus, a newly emerged pest of safflower - Rathod, P K; Mane, P N; Sonalkar, V U (Indian Journal of Plant Protection, 2020)
Field trials were carried out to study the efficacy of some plant products against Gujhia weevil, Tanymecus indicus,a newly emerged pest of safflower in the Vidarbha region of Maharashtra during Rabi season of the years, 2011, 2012 and 2013 at the Oilseed Research Unit, Dr Panjabrao Deshmukh Krishi Vidyapeeth, Akola. The experiment consisted of 13 different treatments and untreated control and was laid out in a randomized block design with three replications. The results based on 3 years of pooled data revealed that phorate 10% G @ 10 kg/ha (at the time of sowing) followed by spraying of chlorpyriphos 20 EC @ 2.5 ml/l of water at 10 days after emergence (DAE) and second spraying of chlorpyriphos 20 EC @ 2.5 ml/l as and when required was found effective against Gujhia weevil and gave highest incremental cost benefit ratio (1:5.1). Second effective treatment was phorate 10% G @10 kg/ha (at the time of sowing) followed by 1st spraying of lambda cyhalothrin 2.5 EC @ 1 ml/l of water at 10 DAE and second spraying as and when required.